Ergonomic Risk Factors and Their Impacts on the Productivity Level of Fashion and Textile Designers in the Kumasi Metropolis, Ghana - Siaw, Stella Daah; Danso, Daniel Kwabena; Adom, Dickson (Graduate School of Institut Seni Indonesia Yogyakarta, 2025)
The working environment setup in small-scale fashion and textile establishments in Ghana face numerous ergonomic risk factors such as low environmental temperatures, noise levels, seating, and ventilation. Due to the continuous precision activities as well as the highly repetitive actions, fashion and textile designers are often exposed to muscle diseases and non-neutral joint postures. This study investigated the impacts of ergonomic risk factors on the productivity of the fashion and textile designers. We used descriptive, cross-sectional and correlational designs under the quantitative research approach to investigate the phenomenon of ergonomic risk factors faced by fashion and textile designers in the Kumasi Metropolis, Ghana. Three hundred and eleven respondents were selected using a random sampling procedure to respond to a closed-ended questionnaire. Additionally, an observation checklist was used to record workers activities at the various workshops. The data were analyzed using descriptive statistics, an independent sample t-test, and correlation. The findings provided strong evidence of the detrimental effects of ergonomic risk factors on the productivity levels of fashion and textile designers in Kumasi Metropolis. The study underscores the need for capacity building in ergonomic risk management to enhance the levels of productivity of fashion and textile designers. Faktor Risiko Ergonomis dan Dampaknya terhadap Tingkat Produktivitas Desainer Mode dan Tekstil di Wilayah Metropolitan Kumasi, Ghana Abstrak Lingkungan kerja yang diatur dalam perusahaan mode dan tekstil skala kecil di Ghana menghadapi banyak faktor risiko ergonomis seperti suhu lingkungan yang rendah, tingkat kebisingan, tempat duduk, dan ventilasi. Karena aktivitas presisi yang berkelanjutan serta tindakan yang sangat berulang, perancang mode dan tekstil sering kali terpapar penyakit otot dan postur sendi yang tidak netral. Penelitian ini menyelidiki dampak faktor risiko ergonomis terhadap produktivitas perancang mode dan tekstil. Kami menggunakan desain deskriptif, cross-sectional, dan korelasional dengan pendekatan penelitian kuantitatif untuk menyelidiki fenomena faktor risiko ergonomis yang dihadapi oleh perancang mode dan tekstil di Kumasi Metropolis, Ghana. Tiga ratus sebelas responden dipilih menggunakan prosedur pengambilan sampel acak untuk menanggapi kuesioner tertutup. Selain itu, daftar periksa observasi digunakan untuk mencatat aktivitas pekerja di berbagai bengkel. Data dianalisis menggunakan statistik deskriptif, uji-t sampel independen, dan korelasi. Temuan tersebut memberikan bukti kuat tentang efek merugikan dari faktor risiko ergonomis terhadap tingkat produktivitas perancang mode dan tekstil di Kumasi Metropolis. Studi ini menggarisbawahi perlunya pengembangan kapasitas dalam manajemen risiko ergonomis untuk meningkatkan tingkat produktivitas perancang busana dan tekstil.